Mechanisms of valuation of public goods on the agricultural land market - considerations in the context of sustainable development = Mechanizmy wyceny dóbr publicznych na rynku ziemi rolniczej - rozważania w kontekście zrównoważonego rozwoju - Czyżewski, Bazyli; Majchrzak, Adam (Zielona Góra: Faculty of Economics and Management Press)
Since the beginning of human civilization, the land has been creating certain utilities which satisfy human needs. When the dangerous side effects of industrial agriculture have occurred intrinsic land utilities are being discovered anew. They have a nature of public goods and constitute a hard core of the sustainable agriculture paradigm. Despite irreversible accumulation of capital in the anthropogenic environment many new utilities of the land come into existence without additional capital and labour outlay. Since they are public goods, they are paid from taxes in great measure. This way an intrinsic land utility takes a form of a financial product and can be called "intrinsic productivity" of land.
Keywords: dobra publiczne; rynek ziemi rolniczej; rozwój zrównoważony; samoistna produktywność ziemi; public goods; agricultural land market; sustainable development; intrinsic land utility